Documento de análisis crítico de un trámite previo a la declaración de recepción de pleno derecho en la contratación pública frente a la seguridad jurídica - Bolaños Cadena, Lady Gisel (2019)
This research study aims to make a critical analysis document that void in article 122 of the Regulations to the Organic Law of the Procurement System, establishing a procedure prior to the de: reception, in order to ensure the principle of legal certainty. This ir been divided into three parts. First, the theoretical foundation, v important aspects on receiving full rights as well as the importance « procedure. The second part is focused on the methodology whict diagnosis on the variables in study. Thus, some interviews and surve in order to solve the problem. Finally, a critical legal analysis has t solved the legal void regarding the previous procedure that must exis reception, since the current regulations are inefficient and deficient agile, flexible and rational reform is required. In the end, it was nece validation of the proposal by experts as well as the general cc recommendations.